Pollution Sensitivity and Resistance Assessment of Native Ornamental Plants for Landscaping in Various Factories - Avilala, Pavan Kumar; Naik, M. Raja; Sreedhar, D.; Padmaja, V. V.; Chakradhar, P. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during 2023–2024 and the data was recorded during post monsoon period (January– February, 2024) to assess the performance of ten native ornamental plants under different pollutants of seven factory sites along with a control in Rayalaseema region of Andhra Pradesh, India, for recommending in green belt development under multiple polluted sites. The data recorded for various parameters under study showed that among the plants tested, Cordyline terminalis at Control site i.e. College of Horticulture reported maximum values for canopy spread (59.54 cm2), leaf extract pH (7.49) and total chlorophyll content (3.86 mg g-1), while it recorded maximum values for ascorbic acid content (13.00 mg g-1), relative water content (89.54%), proline content (9.19 µmoles g-1) and superoxide dismutase activity (4.23 O.D. min-1 g-1) at APMDC factory site. Barleria cristata recorded superior values for Stomatal Index (33.40%) at College of Horticulture (control site) and Chlorophyll stability index (98.04%) at polluted site of APMDC. Phenol content was reported highest in Ixora coccinea (18.96 mg 100 g-1) at mining site (APMDC). Nyctanthus arbor-tristis at APMDC site had reported maximum value for Dust capturing capacity (0.31 mg cm-2). The Data on specific leaf weight showed non significance difference. Cordyline terminalis with superior biochemical traits showed higher Air Pollution Tolerance Index (APTI) values (21.86) at APMDC mining site while, Nyctanthus arbor-tristis with an Anticipated Performance Index (API) grade of 5 has been assessed as a very good performer under polluted sites.